Population dynamics of hepatitis C virus subtypes in injecting drug users on methadone maintenance treatment in China associated with economic and health reform. Issue 7 (1st February 2017) - Zhou, S.; Cella, E.; Zhou, W.; Kong, W.‐H.; Liu, M.‐Q.; Liu, P.‐L.; Ciccozzi, M.; Salemi, M.; Chen, X.
Summary: The extensive genetic heterogeneity of hepatitis C virus (HCV) requires in‐depth understanding of the population dynamics of different viral subtypes for more effective control of epidemic outbreaks. We analysed HCV sequences data from 125 participants in Wuhan, China. These participants were newly infected by subtype 1b (n=13), 3a (n=15), 3b (n=50) and 6a (n=39) while on methadone maintenance treatment (MMT). Bayesian phylogenies and demographic histories were inferred for these subtypes. Participants infected with HCV‐1b and 3a were clustered in well‐supported monophyletic clades, indicating local subepidemics. Subtypes 3b and 6a strains were intermixed with other Chinese isolates, as well as isolates from other Asian countries, reflecting ongoing across geographic boundary transmissions. Subtypes 1b and 3a declined continuously during the past ten years, consistent with the health and economic reform in China, while subtype 3b showed ongoing exponential growth and 6a was characterized by several epidemic waves, possibly related to the recently growing number of travellers between China and other Asian countries. In conclusion, results of this study suggest that HCV subtype 3b and 6a subepidemics in China are currently not under control, and new epidemic waves may emerge given the rapid increase in international travelling following substantial economic growth.